Solitary Renal Metastasis Arising from a Pulmonary Adenoid Cystic Carcinoma: A Case Report and Review of the Literature - Prodromos Philippou; Anastasios Michalakis; Maria Miliatou; Christiana Poullou; Pavlos Constantinou (Case Reports in Urology)
Adenoid cystic carcinoma (ACC) is a malignancy affecting the salivary glands and rarely involving the lung. Due to its rarity, primary lung ACC remains incompletely understood. We herein report the case of a 57-year-old female patient who was initially diagnosed with primary lung ACC and was treated by lobectomy. Seven years later, an abdominal computed tomography scan performed in the context of surveillance revealed the presence of a solid lesion arising from the lower pole of the left kidney. The patient underwent left partial nephrectomy, and histopathology confirmed a completely excised metastatic ACC.